Green-emissive carbon quantum dots with high fluorescence quantum yield: Preparation and cell imaging - WEI, Yingying; CHEN, Lin; ZHAO, Shaoban; LIU, Xuguang; YANG, Yongzhen; DU, Jinglei; LI, Qiang; YU, Shiping (Frontiers of materials science, 2021)
High fluorescence quantum yield (QY), excellent fluorescence stability, and low toxicity are essential for a good cellular imaging fluorescent probe. Green-emissive carbon quantum dots (CQDs) with many advantages, such as unique fluorescence properties, anti-photobleaching, low toxicity, fine biocompatibility and high penetration depth in tissues, have been considered as a potential candidate in cell imaging fluorescent probes. Herein, N, S-codoped green-emissive CQDs (QY= 64.03%) were synthesized by the one-step hydrothermal method, with m-phenylenediamine as the carbon and nitrogen source, and L-cysteine as the nitrogen and sulfur dopant, under the optimum condition of 200 °C reaction for 2 h. Their luminescence was found to originate from the surface state. In light of the satisfactory photobleaching resistance and the low cytotoxicity, CQDs were used as a cell imaging probe for HeLa cell imaging. The results clearly indicate that cells can be labeled with CQDs, which can not only enter the cytoplasm, but also enter the nucleus through the nuclear pore, showing their broad application prospect in the field of cell imaging.